Contribution of Linguistic Skills to Word Reading in DHH Students. (11th April 2022) - Sun, Peng; Zhao, Ying; Chen, Hongjun; Wu, Xinchun
Abstract: This study aims to examine the relative contributions of phonological awareness (PA), orthographical awareness (OA), morphological awareness (MA) and rapid automatized naming (RAN) to word reading accuracy and fluency in Chinese deaf and hard of hearing (DHH) students. Measures of PA, OA, MA, RAN, word reading accuracy, and word reading fluency were administered to 133 DHH and 127 hearing students in Grades 4–6. After controlling for chronological age, hierarchical regression analysis showed that PA made an independent contribution to word reading accuracy and fluency among the DHH students. The unique effect of OA was significant on word reading accuracy in DHH students; whereas, its predictive role was played on word reading fluency in hearing students. RAN accounted for additional variance only in word reading accuracy in DHH students. MA significantly explained the variance in both reading abilities and in both groups. This suggests that for DHH students, they use nonphonological clues (MA and OA) to learn to read. To a lesser degree, however, they do rely on PA to reading words. For hearing students, they mainly rely on MA to their word reading. There are some similarities and differences in the mechanisms underlying word reading in DHH and hearing children.